Pengaruh Skeptisme Profesional, Pengalaman Auditor, Dan Independensi Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan (Studi Empiris KAP Di Kota Jakarta) - Hendardi Aryotama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of professional skepticism, auditor experience and independence on the auditor's ability to detect situations. The population of this study are auditors who worked on the Public Accounting Firm (KAP) in city of Jakarta. The data collectiontechnique in this research used a questionnaire. This type of research is causal associative research. The number of samples collected was 60 people. The sampling technique used was convenience sampling. The results of this research show that: 1) Professional Skepticism has a positive effect on the Auditor's Ability to Detect Fraud. 2) Auditor experience has a positive effect on the auditor's ability to detect fraud. 3) Independence has a positive effect on the Auditor's Ability to Detect Fraud. 4) Professional Skepticism, Auditor Experience, and Independence together influence the Auditor's Ability to Detect Fraud.